The art of peacemaking political essays by Istvan Bibo - Bibo, Istvan (World thought in translation., 2015)
This magisterial compendium of Bibó's essays introduces English-speaking audiences to the writings of one of the foremost theorists and psychologists of twentieth-century European politics and culture.